(Des) conhecimento do Projeto Pedagógico de Curso de Graduação em Medicina entre Estudantes - Menezes , Márcia Mendes; Xavier , Mariza Dias; Dias, Orlene Veloso; Costa, Simone de Melo (Revista Unimontes Científica, 2020)
Medical pedagogical projects are based on competencies and skills described in the National Curriculum Guidelines for that course. Objective: The objective of this work was to analyze the (un) knowledge about the Pedagogical Course Project among medical students. Methodology: Cross-sectional analytical study conducted with academics enrolled in a medical course in the northern state of Minas Gerais. 281 students participated. In the study, students' knowledge about the Course's Pedagogical Project was analyzed. Results: According to the results, there was a lack of knowledge of the Pedagogical Project among students, including the trainees. Conclusion: The findings pointed to the need to elaborate and operationalize the Pedagogical Project in a collaborative and participatory way by all subjects, due to the dialogical praxis between knowledge and action. The need for further studies that may present the impact of these practices on the quality of medical education is emphasized.